9 9 9 9 9 9 8 9 9 9 9 9 9 9 − 9 9 9 9 9 9 8 = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
i think you has the easiest way to solve this problem without writing
I forgot! there's 1 also. hehe, I just solved it mentally and I forgot that there's still 1 in the equation.
nice and easiest way to solve
We can make just like this: (9^9-9^8)/9^8 = 8. Take 999 and write 8 in the end.
Best solution
Gracias amigo
9 9 9 9 9 9 8 9 9 9 9 9 9 9 − 9 9 9 9 9 9 8
= 9 9 9 9 9 9 8 9 9 9 9 9 9 8 × ( 9 9 9 9 − 1 )
= 9 9 9 9 9 9 8 9 9 9 9 9 9 8 × 9 9 9 8 = 1 9 9 9 8 = 9 9 9 8
Your head won't blast. But your calculator totally will.
I find this to be the simplest solution which is how I answered it in my head.
Log in to reply
Well, anyone can do this, just poor for the computer.
I did it like @Michael Fuller, but i really like this approach!
x^2 (x-1)= x^2(x) - x^2(1)= x^3 - x^2
That's distributive property.
9999^999 - 9999^988 = 9999^998 x (9999 - 1)= 9999^998 x (9999) - 9999^998 x (1) = 9999^999 - 9999^998
I probably made a mistake somewhere, but ... Distributive property. Not very intuitive here, but works.
@Jing Sheng you probably know the answer already but...
i don't understand step2. plz do more explanation Thankz. :)
I didn't answer step two too, someone please explain?
9 9 9 9 9 9 8 9 9 9 9 9 9 9 − 9 9 9 9 9 9 8
= 9 9 9 9 9 9 8 9 9 9 9 9 9 8 × ( 9 9 9 9 − 1 )
The ' 9 9 9 9 9 9 8 ' cancels out to give ( 9 9 9 9 − 1 ) = 9 9 9 8
I got the canceling out part but where does the 1 come from? (I would have picked 9999^999 to be the answer but it wasn't an option)
It's easy all of them have the same base so you can subtract the exponents in a division, so the first term of the subtraction after distribuying the division, is 9999^1 and the second term is just 1 so 9999 - 1 = 9998
That was how I solved it. It spared a lot of extra and unnecessary work.
The same as X raised to the power of n. You first take out the LCD of the two terms on the numerator And then you cancel the factors. Then you are left with 9999-1. The answer is 9998.
9 9 9 9 9 9 8 9 9 9 9 9 9 9 − 9 9 9 9 9 9 8 = 9 9 9 9 9 9 8 9 9 9 9 9 9 8 × ( 9 9 9 9 − 1 ) = 9 9 9 9 − 1 = 9 9 9 8
Using the DoTS property gives us 9999^998(9999 - 1) - cancelling the 9999^998. It remains like 9999 - 1, giving us 9998.
In my mind, I did a similar method to what many people below have described
Let A = 9999^998
(9999)A - A
= --------------- A
A (9999 - 1)
= --------------- A
= 9999 - 1
= 9998
9 9 9 9 9 9 8 9 9 9 9 9 9 9 − 9 9 9 9 9 9 8
9 9 9 9 9 9 8 9 9 9 9 9 9 8 ∗ ( 9 9 9 9 − 1 )
9999-1
9998
a n − a n − 1 = ( a − 1 ) a n − 1
The above can be proved through simple distribution on the right side. What we have here is:
a n − 1 a n − a n − 1 = a n − 1 ( a − 1 ) a n − 1 = ( a − 1 )
In this case a is 9999 and n is 999. Regardless, the answer is a - 1, which is 9999 - 1, which is 9998.
Let A=9999^9998
(9999A - A) / A
9998A / A
9998
I split it into two fractions, 9999^999/9999^998 and -9999^998/9999^998. Using the index quotient rule, the first fraction can be evaluated to 9999^1, which is 9999. The second fraction’s denominator and numerator are equal (keep in mind it is negative) meaning it is 1 and so it is 9999 + -1 = 9998
imagine...
2 2 ( 2 3 − 2 2 ) = a
2 3 − 2 2 = 2 2 ∗ a
2 3 = ( 2 2 ∗ a ) + 2 2
2 3 = ( a + 1 ) ∗ 2 2
2 3 / 2 2 = a + 1
2 3 − 2 = a + 1
back to question:
9 9 9 9 9 9 9 − 9 9 8 = a + 1
9 9 9 9 1 = a + 1
9 9 9 9 − 1 = a
9 9 9 8
{(9999^999)-(9999^998)}/9999^998}={(9999^998)(9999-1)}/9999^998=9999-1=9998
9 9 9 9 9 9 8 9 9 9 9 9 9 9 − 9 9 9 9 9 9 8 = 9 9 9 9 9 9 8 9 9 9 9 9 9 8 × ( 9 9 9 9 − 1 ) = 9 9 9 9 − 1 = 9 9 9 8
( (9999^999) - (9999^998) ) / (9999^998) = ( (9999^998)(9999-1) ) / (9999^998) = 9999-1 = 9998
So easy ( 9999^999 - 9999^998 ) / ( 9999^998) = ( 9999^998( 9999 - 1 ) ) / (9999^998) = 9999 -1 = 9998
9999^{999}-9999^{998}/9999^{998} Taking 9999^{998} common in the numerator, we get, 9999^{998}(9999-1)/9999^{998) Cancelling out the like terms, we get, 9999-1=9998
= (9999^998 (9999-1)) / 9999^998 = 9999-1 = 9998
(9999^999 - 9999^998 )/9999^998
=[9999^998×(9999-1)]/9999^998
=9999-1 =9998
9999^9998(9999-1)/9998 = 9999-1 = 9998
(9999^999 - 9999^998)/9999^998 = 9999^998(9999 - 1) /999^998 = 9999 - 1 = 9998
(9999^999-9999^998)/9999^998 = (9999^999/9999^998)-1 = 9999-1 = 9998
x = 9999
-> (x^999 - x^998)/(x^998)
-> (x^999/x^998) - (x^998/x^998)
-> x - 1
= 9999 - 1
= 9998
{9999~998(9999-1)}/9999~998 = 9999-1 =9998
well i just slove it in my head~ no sol hahahaha XD
(9999^999 - 9999^998 )/(9999^998) = ( 9999^999)/ (9999^998) - (9999^998)/(9999^998) = 9999^(999-998) - 9999^(998-998) = 9999^1 - 9999^0 = 9999 - 1= 9998
The same as X raised to the power of n. You first take out the 9999 raise to power 8 of the two terms on the numerator And then you cancel the factors. Then you are left with 9999-1. The answer is 9998.
9999^999 = 9999 * 9999^998 Therefore 9999^999 - 9999^998 = 9998 * 9999^9998. So if you divide by 9999^998 the you're left with only 9998
Problem Loading...
Note Loading...
Set Loading...
9 9 9 9 9 9 8 9 9 9 9 9 9 9 − 9 9 9 9 9 9 8
= 9 9 9 9 9 9 8 9 9 9 9 9 9 9 − 9 9 9 9 9 9 8 9 9 9 9 9 9 8
= 9 9 9 9 − 1 = 9 9 9 8